2007
DOI: 10.1016/j.pbb.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion dose-dependently reverses nicotine withdrawal deficits in contextual fear conditioning

Abstract: Bupropion, a norepinephrine and dopamine reuptake inhibitor and nicotinic acetylcholine receptor antagonist, facilitates smoking cessation and reduces some symptoms of nicotine withdrawal. However, the effects of bupropion on nicotine withdrawal-associated deficits in learning remain unclear. The present study investigated whether bupropion has effects on contextual and cued fear conditioning following withdrawal from chronic nicotine or when administered alone. Bupropion was administered alone for a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 64 publications
2
55
0
Order By: Relevance
“…It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135]. Together, these data suggest that associations between stimuli and the effects of nicotine in humans may contribute to nicotine addiction, and these effects can be modeled in mice by studying the effects of nicotine on contextual learning.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 59%
See 2 more Smart Citations
“…It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135]. Together, these data suggest that associations between stimuli and the effects of nicotine in humans may contribute to nicotine addiction, and these effects can be modeled in mice by studying the effects of nicotine on contextual learning.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 59%
“…Mice withdrawn from nicotine spend less time on the open arms relative to saline controls, indicating increased anxiety [28,77]. Furthermore, nicotine withdrawal-related deficits in contextual learning have been evaluated in mice [33,30,132,133]. Withdrawal-related decreases in the brain reward system in humans has been modeled using the intracranial self stimulation (ICSS) procedure, in which rats press a lever to deliver electrical stimulation to reward-related brain areas.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Other antidepressants, such as bupropion XL (norepinephrine and dopamine reuptake inhibitor, as well as nicotinic antagonist), mirtazapine (noradrenergic and specific serotonergic antidepressant), and trazodone (serotonin-2/1C receptor antagonist), are effective in the treatment of GAD (Bystritsky, Kerwin, Feusner, & Vapnik, 2008;Gambi, De Berardis, Campanella, Carano, Sepede, Salini et al, 2005;Rickels, Downing, Schweizer, & Hassman, 1993). Accordingly, bupropion has anxiolytic effects in the CC model (Portugal & Gould, 2007). Dubovsky, 1990;Milanov, 2007 (-) Propranolol (40 mg Benzodiazepines are very valuable anxiolytics and have long been used to treat anxiety.…”
Section: Predictive Validitymentioning
confidence: 99%
“…Although animal models have been used to examine the somatic and affective symptoms of nicotine withdrawal, less research has focused on the effects of nicotine withdrawal on learning and memory. One behavioral paradigm that has been used to examine the effects of nicotine on learning and memory is contextual fear conditioning [see 31 for review], and studies have consistently shown that acute nicotine enhances contextual conditioning, chronic nicotine does not alter contextual conditioning and nicotine withdrawal disrupts contextual conditioning [16,13,15,32,64,65].…”
Section: Introductionmentioning
confidence: 99%